El arteterapia, un acompañamiento en la creación y la transformación - Bassols, Mireia (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
A definition is contributed of art therapy, a description of its origin and evolution, of the varied origin and formation of its professionals. The work in art therapy is described in relation with the different arts and with its interconnection. Finally, there are described the characteristics of the intervention of the art therapist from a series of fundamental keys.
Keywords: Art therapy; Art therapy evolution; Art therapy formation; Therapeutic intervention